'Searching for Roots': Exploring the Idea of Home in Tibetan Refugee Youth Living in Delhi, India. (September 2021) - Ramanathan, Pallavi; Singh, Purnima
Home is a key aspect of place attachment signified by rootedness and ease; it is operationalised as a sense of being rooted to and feeling at ease in a particular place. Two studies were done to gain a nuanced idea of the concept of home as understood by Tibetan refugee youth living in Delhi. In study 1, based on in-depth interviews on 20 students of ages 18–25 years, a thematic analysis resulted in the global theme of 'community as home' indicating the central position of the community while talking about home. On the basis of this study, four variables were identified as key to the concept of home: in-group identification, group efficacy, social well-being and rootedness (home). Study 2 was designed to understand the relationship between these identified variables. Around 103 refugee youth (controlled for gender) aged 18–25 years completed the questionnaire. It was found that most of the variables were positively correlated to one another, except for group efficacy and social well-being. Further, the mediation analysis indicated that in the context of the community, higher levels of social well-being explained increased in-group identification, particularly when mediated by the presence of group efficacy. Overall, it was found that community seems to be integral to the concept of home for Tibetan refugee youth living in Delhi. Both studies expand upon existing literature on the concept of home and have further implications for the notion of home and the social well-being of Tibetan refugees.